A Qualitative Metasynthesis of the Experience of Fatigue Across Five Chronic Conditions - Jaime-Lara, Rosario B. (J Pain Symptom Manage, 2019)
CONTEXT. Fatigue is a symptom reported by patients with a variety of chronic conditions. However, it is unclear whether fatigue is similar across conditions. Better understanding its nature could provide important clues regarding the mechanisms underlying fatigue and aid in developing more effective therapeutic interventions to decrease fatigue and improve quality of life. OBJECTIVES. To better understand the nature of fatigue, we performed a qualitative metasynthesis exploring patients’ experiences of fatigue across five chronic noninfectious conditions: heart failure, multiple sclerosis, rheumatoid arthritis, chronic kidney disease, and chronic obstructive pulmonary disease. METHODS. We identified 34 qualitative studies written in the last 10 years describing fatigue in patients with one of the aforementioned conditions using three databases (Embase, PubMed, and CINAHL). Studies with patient quotes describing fatigue were synthesized, integrated, and interpreted. RESULTS. Across conditions, patients consistently described fatigue as persistent overwhelming tiredness, severe lack of energy, and physical weakness that worsened over time. Four common themes emerged: running out of batteries, a bad life, associated symptoms (e.g., sleep disturbance, impaired cognition, and depression), and feeling misunderstood by others, with a fear of not being believed or being perceived negatively. CONCLUSION. In adults with heart failure, multiple sclerosis, rheumatoid arthritis, chronic kidney disease, and chronic obstructive pulmonary disease, we found that fatigue was characterized by severe energy depletion, which had negative impacts on patients’ lives and caused associated symptoms that exacerbated fatigue. Yet, fatigue is commonly misunderstood and inadequately acknowledged.